Therapeutic effects of hypoimmunogenic universal human iPSC-derived endothelial cells in a humanized mouse model of peripheral artery disease - Jungju Choi; Nam Gyo Kim; Dasom Kong; Min-Ji Kim; Byeong-Cheol Kang; Daekee Kwon; Da-Hyun Kim; Kyung-Sun Kang (Stem Cell Research & Therapy)
Abstract Background Peripheral arterial disease (PAD) is a leading cause of limb disability due to ischemia caused by atherosclerotic plaques. Cell-based therapies using endothelial cells (ECs) have shown promise in promoting angiogenesis for PAD, but challenges remain in obtaining sufficient ECs from human tissues. Induced pluripotent stem cells (iPSCs) provide a potential solution, though immune rejection issues arise due to human leukocyte antigen (HLA) mismatches. The depletion of HLA class I and II through gene editing aims to broadly avoid lymphocyte recognition and can be achieved by inactivating β2-microglobulin (B2M) and class II transactivator (CIITA). However, B2M inactivation can lead to a ‘missing self’ killing response by NK cells and macrophages. To overcome this, we proposed universal iPSCs by knocking out B2M and CIITA and over-expressing CD24 to reduce immune rejection. Methods Universal iPSCs were tested for their pluripotency and ability to differentiate into ECs. The stimulation of universal iPSC-derived endothelial cells (U-ECs) to T and NK cells was evaluated by activation marker using flow cytometry. We generated a humanized mouse model by intravenously injecting CD34+ hematopoietic stem cells isolated from umbilical cord blood into NSG mice. Finally, we induced a humanized PAD mouse model by removing the femoral artery of the left hindlimb. Then we injected U-ECs, demonstrating the therapeutic efficacy of U-ECs. Results We generated hypoimmunogenic universal iPSC by knocking out B2M and CIITA, along with over-expressing CD24, and confirmed that their pluripotency was maintained. We demonstrated that U-ECs exhibit functional endothelial properties and reduced immunogenicity, effectively mitigating immune recognition from both adaptive and innate immune responses. U-ECs survived in significantly greater numbers after transplantation and elicited a weaker immune response in humanized mice. Then we induced hindlimb ischemia in humanized mice to establish a humanized PAD model. U-ECs induced effective angiogenic capabilities, leading to significant blood flow restoration in ischemic limbs. Conclusions This study demonstrates the feasibility of creating hypoimmunogenic iPSCs and their derivatives that can reduce immune response and function effectively in vivo.